A DETERMINANTS OF GENERATION Z INTEREST IN APPLYING FOR PEER-TO-PEER LENDING CREDIT FACILITIES AT DIGITAL BANKS - Karyadi, M. Nurdian (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This study aims to identify and analyze the factors influencing Generation Z's interest in applying for peer-to-peer (P2P) lending facilities at digital banks. In the rapidly advancing digital era, P2P lending has become an attractive alternative financing option for the younger generation, particularly Generation Z, who are known for their high adaptability to technology. The research employs a quantitative method with data collection conducted through a questionnaire distributed to 200 respondents from Generation Z. Data analysis is performed using multiple linear regression techniques to test the influence of independent variables on interest (dependent variable). The independent variables tested include financial literacy, perceived ease of use, perceived usefulness, and trust. The results indicate that financial literacy, perceived ease of use, perceived usefulness, and trust significantly influence Generation Z's interest in using P2P lending facilities. Perceived usefulness and trust were found to be the most dominant factors affecting Generation Z's decisions. It is recommended that digital banks and P2P lending providers enhance financial education and literacy, develop user-friendly applications, and ensure service transparency and security. Implementing effective marketing strategies through social media and collaborating with educational institutions are also crucial to attract Generation Z's interest. Keywords: Generation Z, Peer-to-Peer Lending, Digital Banks, Interest, Financial Literacy, Perceived Usefulness, Trust.